The Phenomenon of Dynastic Politics Following Constitutional Court Decision Number 33/PUU-XIII/2015 - Febriansyah Ramadhan; Muhammad Saleh; Ratu Julhijah; Ilham Dwi Rafiqi (Sharia and Law Faculty, 2021)
This research aims at breaking down the dynamics of dynastic politics after the 2020 simultaneous general election and the dynamics between the nomination of regional heads and dynastic politics following the issuance of the Constitutional Court decision no. 33/PUU-XIII/2005. The research found that this local politics phenomenon is triggered by the policy on regional autonomy and decentralization after reformation in bringing about new groups with family ties at local levels who occupy positions in the government. Going by the excuses of freedom and human rights, the groups in this dynastic politics have seen a gradual increase in quantity overtime. This increase happened after the Constitutional Court decision no. 33/PUU-XIII/2015 ruled in their favour. In the ruling, the Court took human rights into their main consideration for reversing the ruling against the ban on the dynastic politics law, which in Article 7 (r) UU 1/2015 may give the impression that the right to political participation is removed.